Entrepreneurial networking and sustainability of women-owned micro-enterprise performance: the mediating role of self-organization and entrepreneurial learning behaviors - Mayanja, Samuel Ssekajja; Mutebi, Henry; Isingoma, Juliet Wakaisuka (Emerald, 2025)
Purpose This study examines the mediating role of self-organization and entrepreneurial learning behaviors in the relationship between entrepreneurial networking and sustainability of women owned micro-enterprise performance. Design/methodology/approach We tested our model based on a sample of 518 women-owned micro-enterprises in Eastern Uganda using ordinary partial least squares regression through Smart PLS version 3.3.3. Findings The results show a direct relationship between entrepreneurial networking, entrepreneurial learning behavior, self-organization and sustainability of women owned micro-enterprise performance. In addition, self-organization mediates the relationship between entrepreneurial networking, entrepreneurial learning behavior and sustainability of women owned micro-enterprise performance. Furthermore, entrepreneurial learning behavior mediates the relationship between self-organization and sustainability of women owned micro-enterprise performance. Research limitations/implications The study was cross-sectional; it is possible that the views held by individuals may change over the Originality/value This research contributes to gender-based sustainability of micro-enterprise performance by empirically testing the anecdotal and conceptual evidence.